2018
DOI: 10.1111/1759-7714.12791
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous responses and resistant mechanisms to crizotinib in ALK‐positive advanced non‐small cell lung cancer

Abstract: BackgroundALK‐tyrosine kinase inhibitors (TKIs) have been proven effective for treating ALK‐positive non‐small cell lung cancer (NSCLC), although patients present with variable responses and disease progression courses. The detailed underlying molecular mechanisms require further investigation to yield a better prognosis.MethodsTargeted next‐generation sequencing (NGS) mutation profiling was performed on samples from 42 NSCLC patients confirmed positive for ALK rearrangements by fluorescence in situ hybridizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Intrinsic and acquired resistance mechanisms are highly heterogeneous. In the case of crizotinib, several studies reported mechanisms of acquired resistance mainly involving mutations in the ALK gene (26). In this study, we were able to obtain only one postbiopsy from a patient with acquired resistance and an ALK-G1220R mutation was detected which is known to induce crizotinib resistance.…”
Section: Discussionmentioning
confidence: 93%
“…Intrinsic and acquired resistance mechanisms are highly heterogeneous. In the case of crizotinib, several studies reported mechanisms of acquired resistance mainly involving mutations in the ALK gene (26). In this study, we were able to obtain only one postbiopsy from a patient with acquired resistance and an ALK-G1220R mutation was detected which is known to induce crizotinib resistance.…”
Section: Discussionmentioning
confidence: 93%
“…The most frequently disrupted gene was TP53, even though, due to the low amount of pre-therapy samples to be matched, it is not clear if these mutations may pre-exist the development of resistance. Among other genes, rare private alterations at low frequency were identified in BRAF, FGFR2, MET, NRAS and PIK3CA genes (8,34). Among the others, mutations of POLE gene that encodes the catalytic subunit of DNA polymerase epsilon, permissive of the accumulation of a high number of somatic mutations, have been detected in post-crizotinib specimens (34).…”
Section: Co-occurring Mutationsmentioning
confidence: 99%
“…Among other genes, rare private alterations at low frequency were identified in BRAF, FGFR2, MET, NRAS and PIK3CA genes (8,34). Among the others, mutations of POLE gene that encodes the catalytic subunit of DNA polymerase epsilon, permissive of the accumulation of a high number of somatic mutations, have been detected in post-crizotinib specimens (34). In a post-ceritinib patient-derived cell line a MAP2K1-K57N mutation was identified and it conferred sensitivity to the dual blockade of ALKi plus selumetinib (MEKi) (35).…”
Section: Co-occurring Mutationsmentioning
confidence: 99%
“…33 ALK alterations were detected by Thoracic Cancer 11 (2020) 346-352 fluorescence in situ hybridization with ALK break apart probes and/or immunohistochemistry (IHC) staining with Ventana anti-ALK antibody as previously described. 34…”
Section: Genetic Analysismentioning
confidence: 99%